INTEGRATIVE EDUCATION AS A FRAMEWORK FOR STRENGTHENING TRANSLATORS’ PERFORMANCE IN SITUATIONAL CONTEXTS - Lutfullayev Pulatkhon Mukhibullaevich (Research Focus International Scientific Journal, 2025)
This study investigates integrative education as a pedagogically grounded and conceptually holistic framework for enhancing translators’ performance in situational contexts, while drawing on the methodological traditions of the Uzbek translation school and the scholarly contributions of Professor Gaybulla As-Salom. In contemporary translation training, the growing complexity of professional tasks demands instructional models that extend beyond linguistic proficiency toward situational awareness, technological competence, and intercultural sensitivity. From a pedagogical standpoint, integrative education is rooted in several well-established theories, including constructivism, learner-centered instruction, the competence-based approach, and experiential learning. These theories collectively argue that knowledge is best developed when learners engage in active meaning-making, apply skills in authentic contexts, and integrate cognitive, affective, and practical dimensions of learning. The intellectual heritage of the Uzbek translation school—embodied in the works of Mirtemir, Hamid Olimjon, Shavkat Rahmon, and systematically theorized by Gaybulla As-Salom—reinforces this pedagogical paradigm by emphasizing the inseparability of linguistic form, cultural worldview, and conceptual thinking in professional translation. This corresponds to modern didactic principles advocating for interdisciplinary integration and the development of higher-order thinking skills. Building on these pedagogical and national scholarly foundations, the study implemented a four-week integrative training module that combined scenario-based learning, case studies, role-play simulations, and CAT-tool instruction. Diplomatic negotiations, medical consultation interpretation, and simultaneous interpreting sessions were used as authentic situational environments to operationalize experiential learning and constructivist engagement. Assessment tools—including observational rubrics, diagnostic evaluations, and structured reflective journals—were used to measure pedagogical effectiveness. The findings demonstrate that integrative education, when pedagogically structured, significantly enhances situational competence, rapid decision-making, conceptual awareness, cultural responsiveness, and multimodal information processing. The inclusion of reflection activities aligns with As-Salom’s emphasis on tafakkur (conceptual reasoning) and strengthens metacognitive development. Furthermore, the competence-based pedagogical approach ensures that linguistic, communicative, cultural, and technological skills evolve in a unified and interdependent manner. Overall, the study concludes that integrative education—supported by contemporary pedagogical theories and the methodological insights of the Uzbek translation school—offers a strong, holistic, and culturally grounded model for preparing translators capable of performing effectively in real, high-stakes communicative environments. This approach not only aligns with global standards but also enriches translation pedagogy by connecting national scholarly traditions with modern instructional innovation.